THE USE OF ELECTRIC TRANSFER 448 kHz THERAPY IN SPORTAND IMPACT OF HUMAN MESENCHYMAL STEM CELLS - قصي محمد علي حسين (University of Basrah, 2024)
Mesenchymal stem cells (MSCs) can differentiate into more than one type of specialist cells in our body. They are a potential source of progenitor cells for osteoblasts, chondroblasts, adipocytes, skeletal muscles, and cardiomyocytes. They may also differentiate into ecto- and endodermal cell lines, e.g., neural cells, glial cells, hepatocytes and karetinocytes. Mesenchymal cells represent only 0.001-0.01% of all bone marrow cells, are a crucial population of cells participating in the proliferative phase of damage regeneration, and they are present in nearly all body tissues, the largest number of them is in adipose tissue and blood. Properties of MSCs have formed foundations for a new interdisciplinary field, tissue engineering. Its extensive applications include aesthetic medicine, dermatology, orthopaedics, plastic surgery, physioaesthetics, and sports medicine. The aim of this study is to present selected properties of the mesenchymal stem cells exposed to an electric stimulus of frequency of 448 kHz using Capacitive-Resistive Electric Transfer (CRET) technology